2022
DOI: 10.1038/s41556-022-00880-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the expanding universe of small RNAs

Abstract: mall noncoding RNAs (sncRNAs) are universally distributed in all kingdoms of life-from bacteria and archaea to various eukaryotic organisms 1-3 -and have not ceased to surprise us throughout the last two decades regarding their compositional and functional diversity. Although the definition of 'small' is relatively empirical and subjective in different contexts, in this paper we mainly discuss sncRNAs of 15-50 nucleotides (nt) in length, including the relatively well-characterized small interfering RNAs (siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 129 publications
(165 reference statements)
0
82
0
Order By: Relevance
“…However, survival does not depend on the AGO2 enzymatic slicer activity needed to suppress translation as mice homozygous for a catalytically dead Ago2 ADH allele develop normally [6], suggesting that AGO2 is active through a different mechanism. Besides the cytoplasm, miRNAs also localize to the nucleus [2,7]. They modulate gene expression [2,8,9] and potentially a subset of alternative splices [10][11][12].…”
Section: The Links Between Mirnas and Gene Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, survival does not depend on the AGO2 enzymatic slicer activity needed to suppress translation as mice homozygous for a catalytically dead Ago2 ADH allele develop normally [6], suggesting that AGO2 is active through a different mechanism. Besides the cytoplasm, miRNAs also localize to the nucleus [2,7]. They modulate gene expression [2,8,9] and potentially a subset of alternative splices [10][11][12].…”
Section: The Links Between Mirnas and Gene Regulationmentioning
confidence: 99%
“…Besides the cytoplasm, miRNAs also localize to the nucleus [2,7]. They modulate gene expression [2,8,9] and potentially a subset of alternative splices [10][11][12].…”
Section: The Links Between Mirnas and Gene Regulationmentioning
confidence: 99%
“…The specific cleavage of canonical ncRNAs which produce fragments that functionally mimic miRNAs or directly interact with ribosomes, proteins (such as RNA binding proteins), or other RNAs to modulate gene expression [ 28 , 29 , 30 ]. Although these fragments were initially considered products of degradation and thus ignored in small RNA-seq analysis, the accumulated evidence supports the generation of fragments by specific processing of ncRNA [ 31 , 32 , 33 ]. However, many cases lack known processing factors or defined mechanisms of action, leaving an open field for research ahead.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development of small RNA high-throughput sequencing (HTS) technology, the repertoire of small RNAs was greatly expanded [1][2][3][4][5]. In addition to well-characterized microRNAs and piRNAs, small RNAs were found to be originated from abundant housekeeping non-coding RNAs, such as tRNAs, rRNAs, and snoRNAs [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development of small RNA high-throughput sequencing (HTS) technology, the repertoire of small RNAs was greatly expanded [1][2][3][4][5]. In addition to well-characterized microRNAs and piRNAs, small RNAs were found to be originated from abundant housekeeping non-coding RNAs, such as tRNAs, rRNAs, and snoRNAs [1][2][3][4][5][6]. Recently, ample research has been focused on tRNA-derived small RNAs (tsRNAs) and revealed its diverse functions, including promoting stress-induced translational repression [7,8], mediating epigenetic inheritance of paternally acquired traits [9][10][11], inhibiting cell apoptosis [12] and so on [13,14].…”
Section: Introductionmentioning
confidence: 99%